The Power of Play! A Review of Gamification Design Trends and Their Impact on Learning Outcomes - Haq, Salsabila Thifal Nabil; Prasetya, Didik Dwi; Ichwanto, Muhammad Aris; Samodra, Joko; Prasetya, Luhur Adi (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Digital transformation in education has accelerated the integration of gamification as an interactive and motivational learning strategy. This study presents a systematic literature review following the SPAR 4 SLR protocol, based on the analysis of 25 empirical research articles published between 2020 and 2025. The objective is to explore the distribution and impact of various gamification elements on cognitive, affective, and psychomotor learning domains. Elements that provide rewards, such as points (88%), badges (80%), and leaderboards (72%), were the most commonly applied in learning environments. In contrast, reflective features such as storytelling (20%), learner autonomy (24%), and role-playing activities (16%) were especially effective in increasing emotional involvement, self-directed learning, and practical abilities. Through thematic analysis using NVivo 12, the study found that external rewards often encourage only temporary motivation, whereas reflective components support more lasting and meaningful learning processes. The study concludes by recommending a balanced and goal-oriented approach to gamification design, which can strengthen its role as a transformative educational strategy in the digital learning era.